Birth weight, weight at one year, and left ventricular mass in adult life. Issue 4 (April 1995) - Vijayakumar, M.; Fall, C. H.; Osmond, C.; Barker, D. J.
Abstract : OBJECTIVE--To examine how fetal and infant growth are related to left ventricular mass in adult life. DESIGN--A follow up study of men born during 1920-30 whose birth weights and weights at 1 year were recorded. SETTING--Hertfordshire, England. SUBJECTS--290 men born and still living in East Hertfordshire, England. MAIN OUTCOME MEASURE--Left ventricular mass calculated from measurements of interventricular septal thickness and left ventricular posterior wall thickness and left ventricular internal diameter at end diastole measured by M mode echocardiography. RESULTS--Left ventricular mass was highest in men with the lowest weight at 1 year and fell with increasing weight at 1 year (r = 0.18, P = 0.01). Left ventricular mass was not related to birth weight. The relation with weight at 1 year was independent of factors in adult life known to influence left ventricular mass, including body size, systolic blood pressure, and age. The enlarged left ventricular mass associated with reduced growth in infancy was concentric, affecting both the interventricular septum and the left ventricular posterior wall. Concentric left ventricular hypertrophy is known to be associated with increased death rates from coronary artery disease. CONCLUSION--Low weight at 1 year is associated with concentric enlargement of the left ventricle in adult life. This is consistent with a previous finding of higher mortality from cardiovascular disease in men of low weight at 1 year, and provides further evidence that cardiovascular disease may be partly programmed in early life. The left ventricular enlargement may be a long term result of haemodynamic changes in utero or of persisting changes in growth factor concentrations.